A MODEL OF COLLABORATIVE FOREST RESOURCES MANAGEMENT TO IMPROVE THE PROSPERITY OF POOR FAMILY FARMERS IN EAST JAVA - Nasikh Nasikh (Faculty of Geography, Universitas Gadjah Mada, 2013)
The model of collaborative forest resources management between the local government andpoor Pesanggem families becomes one of important alternative strategies to develop forestssustainably and equitably. The focus of this research is the collaborative forest resourcesmanagement between the local government and Pesanggem farmers. The aim of the researchis to analyze how far the local government and Pesanggem farmer involve in thecollaborative forest resources management. The research is conducted in Pasuruan andMalang. The number of respondent involved in the research is 60 respondents. The researchfinding shows that the participation level of the local government and Pesanggem farmers inthe collaborative forest resources management is quite high. The activities of the respondentsin the collaborative forest resources management are deciding the planting location,planning, evaluating, monitoring, and preparing the seedbed. The income level of Pesanggemfarmers that actively involve in managing the forest resources is also quite high. The averageof their income is Rp 500.000,- up to Rp 650.000,- per month. This means that they give highcontribution to the family income.